Analisis Perbandingan Pengenaan Pajak Penghasilan Final Dan Perhitungan Pajak Penghasilan Non Final Pada UMKM: Studi Kasus Pada Cv Xyz Di Kabupaten Karawang - Seli Marlina; Lilis Lasmini; Fista Apriani Sujaya (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was conducted to make a comparison between the imposition of non-final tax and final tax in calculating corporate income tax on CV. XYZ for research materials in its calculations uses data in 2022. The research method in this article is to use descriptive qualitative research, based on the phenomenon being studied and interviews with research sources. From this research it can be concluded that when calculating Non-Final Income Tax on CV. XYZ the resulting value is smaller than the Final Income Tax calculation on CV. XYZ, this difference shows that although Final PPh is greater than Non-final PPh, in terms of the rules and calculations of Final PPh it is simpler. And also the Final Income Tax calculation is more efficient even though the tax value is greater.